Assessment of Digital Activity of the Population in the Context of the Theory of Generations - M. V. Bikeeva (Статистика и экономика)
Purpose of the study. Digital reality dictates the need to develop a new block of competencies - digital skills. For employment and subsequent career growth, knowledge of computer technology, programming skills and the use of software are of high importance. For a high-quality daily life of different age categories of the population, competencies in the use of personal computers, the Internet and other types of ICT are required. In the context of the rapid expansion of the Internet audience, it is of particular interest to assess the activity of the population in the digital space and analyze the purposes of its use. The materials of the article touch upon the theory of generations, which reveals patterns in the behavior of people born in the same time intervals. Representatives of different generations under the influence of economic, political, social and cultural factors form their own values and perception of the world. Which, ultimately, will require the adaptation of both the consumer goods and services market and the labor market to the characteristics of representatives of each generation. This predetermines the need to study the specifics of the use of the digital environment by representatives of the designated economically active generations.Materials and methods. The information base of the study was the data of the Federal State Statistics Service for 2012–2019, as well as the results of sample surveys of households on the use of ICT. As a tool for assessing the digital behavior of representatives of economically and socially active generations, statistical methods were used: comparative analysis and analysis of time series.Results. The age structure of the population of the Russian Federation is represented by the following generations: the baby boomer generation, generations X, Y and Z. The share of these economically and socially active generations is 95% of the total population of the country. The share of the greatest and silent generations is 5%. Each generation has its own patterns of behavior. Comparative characteristics of the features of the use of the digital environment led to the conclusion that for all generations the priority goals of using the Internet are communications and personal interaction. The main differences are manifested in the specifics of actions performed by representatives of the generations under consideration on the Internet and consumer preferences for goods and services presented on different digital platforms. At the same time, representatives of generation Z have a higher level of digital skills compared to representatives of other generations. The results of the study are of interest to business representatives when developing strategic directions for interacting with consumers and subsequently involving a significant part of society in the online space.